Effects of Covid-19 pandemic on maternity staff in 2020 : a scoping review - Nadine Schmitt; Elke Mattern; Eva Cignacco; Gregor Seliger; Martina König-Bachmann; Sabine Striebich; Gertrud M. Ayerle (BMC health services research, 2021)
In the spring of 2020, the SARS-CoV-2 virus caused the Covid-19 pandemic, bringing with it drastic changes and challenges for health systems and medical staff. Among the affected were obstetricians and midwives, whose close physical contact with pregnant women, women who recently gave birth, and their children was indispensable. In the obstetric setting, births cannot be postponed, and maternity staff had to adapt to assure obstetric safety while balancing evidence-based standards with the new challenges posed by the pandemic. This scoping review gives a comprehensive overview of the effecs the Covid-19 pandemic had on maternity staff. We followed the evidence-based approach described by Arksey & O’Malley: we searched several databases for English and German articles published between January 2020 and January 2021 that discussed or touched upon the effects the pandemic had on maternity staff in OECD countries and China. We found that structural challenges caused by the crisis and its subjective effects on maternity staff fell into two main topic areas. Structural challenges (the first main topic) were divided into five subtopics: staff shortages and restructuring; personal protective equipment and tests; switching to virtual communication; handling women with a positive SARS-CoV-2 infection; and excluding accompanying persons. The pandemic also strongly affected the staff’s mental health (the second main topic.) Attempting to meet challenges posed by the pandemic while afraid of contamination, suffering overwork and exhaustion, and struggling to resolve ethical-moral dilemmas had severe negative subjective effects. Several studies indicated increased depression, anxiety, stress levels, and risk of post-traumatic stress symptoms, although the crisis also generated strong occupational solidarity. Care for pregnant, birthing, and breast-feeding women cannot be interrupted, even during a pandemic crisis that requires social distancing. Maternity staff sometimes had to abandon normal standards of obstetric care and were confronted with enormous challenges and structural adjustments that did not leave them unscathed: their mental health suffered considerably. Researchers should study maternity staff’s experiences during the pandemic to prepare recommendations that will protect staff during future epidemics.
Keywords: Covid-19 pandemic; Scoping review; maternity staff; midwife; obstetrician; child; pandemics; Parturition; Pregnancy; SARS-CoV-2